ENKD1 attenuates antibacterial immunity by facilitating TRIM21-mediated RUBCN degradation to suppress LC3-associated phagocytosis - Caimeng Song; Lulu Sun; Jie Wang; Shujun Liu; Wenqing Xu; Cai Zhang; Jun Zhou; Tianliang Li; Yan Li (Proceedings of the National Academy of Sciences, 2025)
Microtubule-associated protein 1A/1B-light chain 3 (LC3)-associated phagocytosis (LAP) plays a critical role in host defense against invading pathogens, including Listeria monocytogenes ( Listeria. monocytogenes ) , Salmonella typhimurium ( S. typhimurium ) , and Francisella novicida ( F. novicida ) . However, the precise regulatory mechanisms controlling LAP remain poorly understood. Here, we identify enkurin domain-containing protein 1 (ENKD1) as a key negative regulator of LAP during infection with these pathogens. Macrophages infected with L. monocytogenes (10403S), S. typhimurium (ATCC14028), or F. novicida (U112) exhibit significant ENKD1 downregulation. ENKD1-deficient macrophages display enhanced antibacterial activity, characterized by increased LAP, higher reactive oxygen species production, enhanced LC3 lipidation on phagosomes, and improved phagosome-lysosome fusion. In vivo, ENKD1 - deficient mice ex hibited improved bacterial clearance in the liver and spleen, with notable survival benefits. Mechanistically, ENKD1 interacts with the E3 ubiquitin ligase tripartite motif-containing protein 21 (TRIM21), which mediates degradation of Run domain Beclin-1-interacting and cysteine-rich domain-containing protein (RUBCN) through K48-linked polyubiquitination, thereby dampening RUBCN’s role in LAP. Our findings reveal an ENKD1–TRIM21–RUBCN axis that suppresses LAP, providing insights into antibacterial immune regulation and suggesting potential therapeutic strategies to enhance host defense against intracellular pathogens.